Kinetics and Mechanisms of Cadmium (Ii) Ion Sorption Using Carbonized and Modified Sorghum (Sorghum Bicolor) Hull of Two Pore Sizes (CMSH 150µm and 250µm) - Imaga, C; A.A, Abia (International Journal of Chemical and Process Engineering Research, 2015)
Aim of this study was to investigate the use of modified and carbonized Sorghum Hull of two different pore sizes (150µm and 250µm) in the removal of Cadmium (II) ion from aqueous solution. The effect of contact time (20, 40, 60, 80 and 100) minutes were investigated, reported and analysed accordingly. The maximum adsorption for 150µm and 250µm were at 80th and 40th minutes, respectively (54.895mg/l and 58.874mg/l). Kinetic modeling of the results of Cadmium (II) ion of both pore sizes were also investigated, reported and analysed. These results showed that Pseudo second order kinetic model best described the sorption process. The Mechanism of sorption showed that CMSH 150µm and 250µm, respectively were particle diffusion controlled. This will serve as parameters to consider in the design of treatment plants for heavy metal detoxification using biosorbents of different pore sizes.